Development of Tamhidi Qira'ah Teaching Materials Based On Character Education - Irhas, Moh; Pujiati, Tri (UIN Syekh Wasil Kediri, Indonesia, 2024)
An ideal Arabic language learner needs high-quality teaching materials. In other words, the teaching materials become a learning resource that is easy for students to understand and can instill character education within them. In reality, one of the problems in Arabic language learning is the students' lack of understanding in comprehending reading materials (Qira’ah) and teaching materials that incorporate character education values. Therefore, this research is interested in developing teaching materials that encompass character education values within them. By integrating character education values into teaching materials, it aims to enhance students' knowledge, skills, and attitudes. This research aims to produce Qira’ah Tamhidi teaching materials based on character education and to determine the feasibility of Qira’ah Tamhidi teaching materials based on character education in learning. The type of this research is Research and Development (R&D) with the ADDIE development model. The data analysis technique used is the quantitative descriptive technique. Based on the results of validation by subject matter experts, design experts, and student responses, the feasibility of the character education-based Qira'ah Tamhidi teaching materials is very good and suitable for use in learning.